Measure Solar System Objects and Their Movements for Yourself! - Clark, John D. (The Patrick Moore Practical Astronomy Series, 2009)
Instead of taking somebody's word about the basic size and distances for the solar system's objects, this book shows amateur astronomers how to measure these things for themselves. This is an enriching experience for any amateur astronomer - to understand and personally measure fundamental astronomical quantities and distances. A basic knowledge of geometry is required, but it is amazing how simple the ideas can be. Readers are led through the details as gently as possible - and in a light-hearted way - presuming that most will have half-forgotten most of the mathematics. The practical astronomical equipment recommended is no more than a typical commercially-made amateur telescope and a camera of some sort - these days a webcam works very well. Apart from that all the reader will need is access to a computer with internet service, the know-how to download free software, and an enthusiasm to expand his knowledge of the basics of scientific astronomy.